(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
This study examines the Muslim community in learning religion, emphasizing the necessity of having a guiding teacher. A teacher or ustad will convey religious messages effectively and through behavior that is already actualized in daily life. Urban millennial Muslims lack the space and time for direct guidance from a teacher. This is due to the high mobility and busy schedules of parents outside the home, leading millennials to prefer instant and easy solutions. Religious or spiritual counseling is done in a very simple and time-saving manner. They often use YouTube and other social media content to enhance their spirituality, akin to shopping at a supermarket. Supermarket shopping provides convenience in fulfilling human needs by offering a complete stock of food and necessities without having to switch stores to get all desired items. Transactions at supermarkets are also straightforward, with debit or credit cards, even virtual money, completing the transaction easily and legitimately. Thus, this phenomenon becomes an analogy for selfservice religiosity among urban millennials. This research uses sequential descriptive methodology with characteristics of qualitative research. Sequential descriptive research refers to continuous descriptive work on a research subject